The power of place contentious politics in twentieth-century Shanghai and Bombay - Frazier, Mark W. (Cambridge, [England] Cambridge University Press, 2019)
"The Power of Place Riots, strikes, and protests broke out in the streets of Shanghai and Bombay, renamed Mumbai in 1995, with impressive frequency during the twentieth century. Many of the landmark protests and social movements had close connections with the neighborhoods, workplaces, and civic space of each city. By the late twentieth century, as the political geography of each city changed rapidly with the commodification of urban land, so too did the patterns of political contention. Using a comparative historical lens, Frazier chronicles the political biographies of these two metropolises and leading centers of manufacturing and finance. Debates over ideology, citizenship, and political representation took material form through clashes over housing, jobs, police violence, public space, among much else in the lived experience of urban residents. Frazier puts contemporary debates over informal housing, eviction of inner-city residents, scarcities of manufacturing jobs, and questions of unequal citizenship in illuminating historical context."--Provided by publisher.
Introduction: Urban citizenship and urban political geography--Inequalities in context--Urban protests and urban social movements--Ideogies ans institutions--Urban historical comparisons--Organization of chapters-- 1. Political geographies and contentious ports: Port cities of the British Imperium--Urban Sovereignty--Migration and citizenship--Civic spaces--Residential spaces--Consumers: City and Nation--Texitle districts-- 2. Nationalism and urban social movements, 1919: Shaghai and the May fourth movement--Bombay: separate mobilizations, segmented citizenship--Consuming citizenship: National products movements bombay-- 3. Containing contention through nationalist movements: The high tide of Urban citizenship in Shanghai, 1925-1927--Community, class, and Nation in bombay--State-building and War: Shanghai in the 1930s and 1940s--Controlled contention under Congress: Bombay in the 1930s and 1940s-- 4. The quest for a socialist-modernist metropolis: Bombay: Urban planning confronts the past--Shanghai: Spatial legacies and Political transformations-- 5. The rebellions of 1966: Shivaji's Army--Worker rebels in Shanghai-- 6. Relocation, de-industrialization, and the Politics of compensation in Mumbai: The Politics of planning: reclamation and relocation--the last textile strike in Bombay--the riots of 1992-1993--from Bombay to Mumbai--operations Shanghai-- 7. Relocation, de-industrialization, and the Politics of compensation in Shanghai: The hated '80s: late Socialist Shanghai and its discontents--Longtou: "Head of the Dragon"--Land-Led deindustrialization--relocation, compensation, and contentious Politics.
Includes bibliographical references (pages 267-284) and index.
Keywords: Sociology, Urban -- China -- Shanghai; Sociology, Urban -- India -- Mumbai; Gentrification -- China -- Shanghai -- History -- 20th century; Gentrification -- India -- Mumbai -- History -- 20th century; Social movements -- China -- Shanghai -- History -- 20th century; Social movements -- India -- Mumbai -- History -- 20th century; Urbanization -- China -- Shanghai -- History -- 20th century; Urbanization -- India -- Mumbai -- History -- 20th century; Mumbai (India) -- Social conditions -- 20th century; Shanghai (China) -- Social conditions -- 20th century